Understanding university students' self-directed online learning in the context of emergency remote teaching: the role of online learning readiness and digital literacy - Alanoglu, Muslim; Karabatak, Songul; Yang, Hongwei (Springer, 2025)
Digital literacy encompasses the skills needed to effectively navigate and use the digital tools and resources that are essential in today's educational landscape. Students with higher levels of digital literacy often demonstrate self-directed learning skills, enabling them to manage their study schedules and submit assignments in a timely and effective manner. Integrating digital literacy with preparation for self-directed learning is critical to fostering successful online learning experiences. Research into the impact of students' digital literacy and readiness for online learning on their self-directed learning is crucial to understanding the competencies and skills required for online education. Such competencies in learners may have unique effects, especially in specific online learning processes such as emergency remote teaching. Therefore, this study aimed to explore the potential impact of students' digital literacy on their self-directed online learning, with a particular focus on their online learning readiness. In line with the purpose of the study, a cross-sectional survey design was employed, using a structural equation modeling approach. The results showed that digital literacy has a direct and positive effect on online learning readiness. In addition, online learning readiness has a direct and positive influence on self-directed online learning. The results also highlighted that digital literacy indirectly and positively influences individuals' levels of self-directed online learning through their online learning readiness.
Keywords: Distance education and online learning; Twenty-first century abilities; Information literacy; Teaching/learning strategies